2014
DOI: 10.1209/0295-5075/108/46003
|View full text |Cite
|
Sign up to set email alerts
|

Signature of topological quantum phase transitions via Wigner-Yanase skew information

Abstract: We apply the Wigner-Yanase skew information approach to analyze two typical models that exhibit a topological quantum phase transition. Based on the exact solutions of the ground states, the Wigner-Yanase skew information between two nearest sites for each of the two models is obtained. For the one-dimensional Kitaev chain model, the first-order derivative of the Wigner-Yanase skew information is non-analytical around the critical point. The scaling behavior and the universality are verified numerically. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Cheng et al [217] showed a finite-size scaling ansatz for the first derivative of the local quantum coherence analogous to the one used for the two-qubit concurrence. Similar results have also been obtained for the extended Fermi-Hubbard model by means of DMRG calculations [218] and for topological quantum phase transitions in the 1D Kitaev chain and in the 2D Kitaev honeycomb model [219]. The finite temperature scaling of the WYSI was analysed in [220] for infinite XY chains using a similar scaling ansatz which allows one to collapse on the same curve data obtained for different temperatures.…”
Section: Quantum Coherence-based Correlations and Wigner-yanase Skew ...supporting
confidence: 66%
“…Cheng et al [217] showed a finite-size scaling ansatz for the first derivative of the local quantum coherence analogous to the one used for the two-qubit concurrence. Similar results have also been obtained for the extended Fermi-Hubbard model by means of DMRG calculations [218] and for topological quantum phase transitions in the 1D Kitaev chain and in the 2D Kitaev honeycomb model [219]. The finite temperature scaling of the WYSI was analysed in [220] for infinite XY chains using a similar scaling ansatz which allows one to collapse on the same curve data obtained for different temperatures.…”
Section: Quantum Coherence-based Correlations and Wigner-yanase Skew ...supporting
confidence: 66%
“…Thus, they are characterized by the change in some topological properties in the ground state of the system. Attacking this problem with the tools of quantum information theory has also given some important insights about the nature of the topological phase transitions [88][89][90][91][92][93].…”
Section: Behavior Of Correlationsmentioning
confidence: 99%
“…Traditionally, a QPT is described in the framework of the Landau-Ginzburg paradigm that the transition from one phase to another is usually accompanied by symmetry breaking. In recent years, many works paid attention to this problem from the quantum information perspective [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (e.g. fidelity [16,17], quantum echo [18], quantum quench dynamics [20]).…”
Section: Introductionmentioning
confidence: 99%